Willingness to pay for what? Testing the impact of four factors on willingness to pay for facilitating and sanctioning energy policy instruments - Kim, Sohee; Kim, Seoyong (Energy Reports, 2023)
The purpose of this study is to analyze individuals’ willingness to pay (WTP) for energy policies. The type of energy policy was divided into facilitating and sanctioning instruments. We studied the factors that influence WTP for two types of intrument for energy policy by using four theoretical frameworks: the Economic Model, the Theory of Planned Behavior, Value Theory, and Psychometric Paradigm (so called risk perception model). The results, first, showed that the WTP for the sanctioning instruments was lower than that for the facilitating instruments. Second, the values, trust, and norms were significant predictors of the WTP for both types of policy instruments. Third, the economic factors only influenced the WTP for sanctioning instruments. This study recommends policy mix considering the WTP for different types of instruments for energy policy.
Keywords: Behavior values; Economic models; Facilitating and sanctioning instrument; Perception model; Policy instruments; Psychometric paradigm; Theoretical framework; Theory of Planned Behavior; Value theory; Willingness to pay; Energy policy; Facilitating and sanctioning instrument; Policy instrument; Willingness to pay